The logarithm of a number is the value that should raise the base to obtain this number. For example, the logarithm of the unit, with a base 10, is zero because the number 10 to the zero power is equal to unity.

With this in mind and considering that our base is 3, we take the above expression and pose:

Log_3(x + 1)^2 = 2

3^2 = (x + 1)^2

Taking the square root of both sides:

x + 1 = 3

x = 3 – 1

x = 2

Based on the initial explanation we make a verification. The base of the logarithm is 3, then we have:

3^2 = (x + 1)^2

9 = (2 + 1)^2

9 = 9

**So that the value of x in our equation is x = 2**

When you take the square root, you will get two answers. In this case, -4 is another solution.

The graph:

Log3(x+1)2=2

You use the law of log that is a power will be brought down to make the log look as follows:

2Log3(x+1)=2

Then you divide both sides by 2

Log3(x+1)=1

3=x+1

3-1=x

2=x